Telaah Terhadap Praktik Akad Wadi’ah Di Perbankan Syariah - Ayif Fathurrahman (Universitas Islam Lamongan, 2019)
Even though Islamic banking through its programs has socialized sharia products to the general public, there are still some people who do not understand a number of sharia products, even though when examined about the benefits, all Islamic products certainly have their respective functions and roles in the economic life of the people. In connection with it, the products of the Islamic bank does not escape the problems. In practice, there are findings that might reduce the level of public interest if allowed to continue without the actions of Islamic banks. In addition, even in a sharia perspective, it is necessary to review how the contract should be implemented so that it does not harm both parties, both the bank and the customer. The article intends to examine more deeply about one of the sharia products, namely wadi>’ah (safekeeping services). This product is a deposit fund service where depositors can take the funds at any time, where the bank is not obliged but is allowed to give bonuses to customers. In this paper, the author tries to trace the wadi>’ah contract and its application in Islamic banking and tries to analyze the basis agreed upon by the National Sharia Board (DSN). Based on the literature review and the application of wadi>’ah in Islamic banking, the authors conclude for a while that there is nothing that shows a discrepancy with Islamic principles. However, in practice, it is still very necessary to develop. Keywords: Wadi>’ah, Islamic Bank, National Sharia Board